2015
DOI: 10.1007/s13277-015-3741-3
|View full text |Cite
|
Sign up to set email alerts
|

High serum levels of extracellular vesicles expressing malignancy-related markers are released in patients with various types of hematological neoplastic disorders

Abstract: Many cell types release extracellular vesicles (EVs), including exosomes, microvesicles (MVs), and apoptotic bodies, which play a role in physiology and diseases. Presence and phenotype of circulating EVs in hematological malignancies (HMs) remain largely unexplored.The aim of this study was to characterize EVs in peripheral blood of HM patients compared to healthy subjects (controls). We isolated serum EVs from patients with chronic lymphocytic leukemia (CLL), non-Hodgkin's lymphoma (NHL), Waldenstrom's macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
151
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 61 publications
12
151
0
3
Order By: Relevance
“…In constrastsystemic administration via intravenous 131 infusion affords the provision for repeated exosome dosage but may carry the risk of ‘off target effects’ in other organs besides the heart. Similarly, it has been shown that intracoronary transfer of stem cells results in migration of the cells across the vessel barrier and into the neighboring myocardium 132, 133 providing the rationale for a similar delivery method for exosomes in the future. Optimal exosome based treatment would warrant ‘ tailored exosomes’ designed for specific cell types within an organ to minimize adverse effects but this approach has not been tested yet and certainly represents a limitation.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 98%
See 1 more Smart Citation
“…In constrastsystemic administration via intravenous 131 infusion affords the provision for repeated exosome dosage but may carry the risk of ‘off target effects’ in other organs besides the heart. Similarly, it has been shown that intracoronary transfer of stem cells results in migration of the cells across the vessel barrier and into the neighboring myocardium 132, 133 providing the rationale for a similar delivery method for exosomes in the future. Optimal exosome based treatment would warrant ‘ tailored exosomes’ designed for specific cell types within an organ to minimize adverse effects but this approach has not been tested yet and certainly represents a limitation.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 98%
“…Indeed, it is reported that routine examination of serum from patients with different malignant disorders reveals high expression of extracellular vesicles that display malignancy-related disorders 133 . Similarly, cardiac hypertrophy has been associated with release of exosome from the heart that carry functional angiotensin II type I receptor (AT1R) 137 .…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…The results showed that the number of extracellular vesicles was substantially higher in the prostate cancer patient group than in the healthy control group. Caivano et al [22] used flow cytometry to count the number of microvesicles and showed that the number was higher in subjects with hematological malignancies than in healthy individuals. The number of exosomes/microvesicles is useful not only as a diagnostic marker of tumors but also as a marker of progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Jóval kevesebb vizsgálat folyt hematológiai malignitások és az extracelluláris vesiculák kapcsolatára vonatkozóan [20,[26][27][28][29]. Ezeket mutatjuk be összefoglalónk hátralévő részében.…”
Section: áBraunclassified
“…Diagnóziskor és a kezelés egyes szakaszai során, majd a kezelés végén AML-es betegek véréből nyert exosomák fehérjemintázata jellegzetes különbségeket mutatott. E közlemények felvetik, hogy az extracelluláris vesiculákat biomarkerként hasznosíthatnánk hematológiai malignitások diagnosztikájában, a maradék betegség kö-vetésére [18,26,29,37]. A vér vagy a vizelet vesiculáinak vizsgálata lényegesen kevésbé invazív mintavételt igényel-ne, mint sok más, jelenleg rutin-vizsgálóeljárás.…”
Section: Extracelluláris Vesiculák Aml-ben Mint Potenciális Biomarkerekunclassified